Narratives of Conflict on TikTok: Comparing the EU and China’s Discursive Strategies in the Israel–Hamas Conflict (Revista de Estudios Europeos, 2026)
This study compares the narrative strategies of two international media outlets with contrasting institutional profiles: CGTN Europe, a state-run channel affiliated with the Chinese government, and Euronews, a pan-European broadcaster currently under private ownership, with an editorial line that remains independent. Based on a mixed-methods approach combining lexical analysis using TF-IDF, thematic clustering with BERTopic, and qualitative video analysis (including shot-by-shot examination), the study identifies key differences in the representation of the Israel–Hamas conflict on TikTok. CGTN Europe constructs a narrative that emphasizes the humanitarian dimension of the conflict, highlighting the impact on the civilian population in Gaza and advocating for a ceasefire, in alignment with the diplomatic positions expressed by the Chinese government in international forums. Euronews, by contrast, tends to adopt a more diverse discursive strategy, focused on the evolution of events and modular coverage rather than emotional repetition. This approach reflects its institutional commitment to editorial pluralism and informational neutrality. At the same time, securitization frames are also present, particularly in conflict-related contexts, where issues such as institutional stability, public order, and international law are emphasized. TikTok, with its algorithmic and emotionally driven logic, thus emerges as a strategic space in which media actors project micro-narratives adapted to the platform.